Intergenerational Risk Sharing with Market Liquidity Risk - Daniel Dimitrov (Tinbergen Institute, 2022)
This paper examines the optimal allocation of risk across generations whose savings mix is subject to illiquidity in the form of uncertain trading costs. We use a stylised two-period OLG framework, where each generation makes a portfolio allocation decision for retirement, and show that illiquidity reduces the range of transferable shocks between generations and thus lowers the benefits of risk-sharing. Higher illiquidity then may justify higher levels of risk sharing to compensate for the trading friction. We still find that a contingent transfers policy based on a reasonably parametrised savings portfolio with liquid and illiquid assets increased aggregate welfare.
Keywords: G11; G23; E21; H55; 330; intergenerational risk sharing; (il)liquidity; stochastic overlapping generations; funded pension plan